Laser powder bed fusion of Ti6Al4V lattice structures and their applications - Dzogbewu, Thywill Cephas (Journal of Metals, Materials and Minerals, 2020)
The study focused on producing lattice structures using rhombic and diagonal nodes and indicating their logical biomedical and engineering applications. Laser powder bed fusion manufacturing technology a subset of additive manufacturing was used to manufacture the lattice structures with different struts geometry. Average elastic modulus value of 5.3±0.2 GPa was obtained for the rhombic lattice structures and 5.1±0.1 GPa for the diagonal lattice structures. Generally, the mechanical properties of the lattice structures produced could be logically considered suitable for biomedical and engineering applications. The mechanical properties of the lattice structures could be fine-tuned for a specific engineering or biomedical applications by varying the lattice properties of the lattice structures.